Application of Monte Carfo Simulation Method for Forecasting Discharge of a Stream Flow - . Oktafri (PERTETA, 2001)
Discharge of a stream flow is one process in hydrologic cycle. Fluctuation of discharge - directly or indirectly - is more affected by rainfall intensity. Because rainfall intensity is dependent on weather (climate), discharge will be fluctuated dependent on change of weather (climate). In a long period (for example 10 years), data of discharge will become a data series. A data series of discharge is a stochastic data. There are two aspects in a data series, i.e. probability aspect and time aspects. A data series can be simulated with based on stochastic concept. One of the methods that can be used is Monte Carlo Simulation Method. Furthermore, in this paper will be exposed the resuff of accurateness of Monte Catlo Simulation Method to simulate data series of discharge. Mean weekly data series of discharge of Cikapundung stream flow (Cigulung-Cikapundung sub watershed in North Bandung - West Java), were used.